Australia's Proposed Exercise in Contract Law Reform: International Convergence and Regional Implications - BITAS, Basil C. (Institutional Knowledge at Singapore Management University, 2013)
In July 2012, the Australian Attorney-General’s Department began soliciting comment regarding the best way to reform Australian contract law to render it more suitable for the demands of 21st century commerce. The effort marks an appreciation of the changing commercial environment and challenges the traditional common law preference for piecemeal, organic reform through case law. The proposed effort has implications for the global convergence of legal systems and further poses practical questions as to what form any such contractual reform should take. Codification in the European, civil law sense is a possible but unlikely outcome. A persuasive but non-binding restatement of law offers flexibility, but may add to confusion where the dominant doctrinal trend is not evident, thereby leading to the question of “what” to restate. Accordingly, there are clear obstacles to the process. This commentary suggests, however, that these obstacles should not be allowed to undermine the effort. With the growing scope and intensity of cross-border trade, parties from disparate legal systems are interacting with each other in ever-closer commercial proximity. Exercises aimed at rendering the common law less opaque and easier to navigate can contribute to the development of the common grammar necessary to facilitate this interaction. The end point of Australia’s reform process may not be clear, but an exercise aimed at “rationalising” certain aspects of common law doctrine through a process of organised reform may be an idea whose time has come. This commentary sketches out some of the key considerations from a comparative, practical and global perspective, highlighting in the process the relevance of such reform efforts to the region.